Replicable success cases of technological interventions under Farmer FIRST project in Uttar Pradesh - Sah, Uma; Rani, Rekha; Singh, Vikrant; Ojha, Jitendra; Dubey, S K; Singh, Bansa (Indian Farming, 2022)
The successful results of the farm interventions demonstrated higher yield potential of the introduced hybrid/varieties in the project area. These results are expected to contribute to significant area enhancement under the introduced technology in the project areain the coming years. Thus, ICAR's one of the most ambitious projects, the farmer FIRST Programme has marked its role in the socio-economic upliftment of the partner farmers in Fatehpur district and paved the way for many more success stories ahead.